Visual appearance of unpainted wood: mould coverage, lightness and uniformity. (2nd January 2019) - Lie, Solrun Karlsen; Vestøl, Geir I.; Høibø, Olav; Gobakken, Lone Ross
ABSTRACT: This study addresses changes in visual appearance of unpainted wood materials exposed outdoors. Specimens of aspen ( Populus tremula ), Norway spruce ( Picea abies ), untreated Scots pine ( Pinus sylvestris ), DMDHEU-modified Scots pine and acetylated Radiata pine ( Pinus radiata ) were exposed facing south in Ås, Norway for 62 weeks. During this period, mould growth coverage, lightness ( L *) and the uniformity of the weather grey colour were assessed. Mould growth coverage was evaluated visually using a rating system. L * and the uniformity were evaluated using image analysis. The increase in mould rating of the wood materials developed in varying speed, but all specimens had reached the maximum rating after 42 weeks. Until then, the changes in L * correlated significantly with the mould rating. However, the specimens continued to darken after they had reached maximum mould rating. DMDHEU was the only material that obtained a more uniform colour as a consequence of the weathering.